THE EFFECTIVENESS OF LINEAR SYSTEM MEDIA ON THE THREE VARIABLE LINEAR EQUATION LEARNING SYSTEM - Silvana, Ari Wahyu; Utomo, Dwi Priyo; Ummah, Siti Khoiruli (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
The aim of this study described the effectiveness of instructional media that produces valid, effective, and practical media. The development of communication and technology requires teachers to be more active and creative in carrying out classroom learning. Teachers can develop learning media that can improve student learning outcomes. The sample of this research trial was the students of class X at MAN 1 Mojokerto. This study uses a 4-D research method which is shortened to 3-D. Data collection techniques used include interviews with mathematics teachers, pretest and posttest questions. The instruments used in this study include guidelines for using media, teaching materials, validation sheets, student response questionnaires and tests. The results of this study indicate that the average validation guide for the use of media, and teaching materials is 95.15%, besides that the validator also provides an assessment on the response questionnaire sheet of 97.5%. This indicates that the media guidelines, teaching materials, and response questionnaires are very valid. The average result of the N-Gain value of students is 0.96, based on the N-Gain criteria scale shows high criteria so that the media is said to be effective, and the results of the calculation of students' questionnaire responses show that each statement point is greater by 70% and the students can be said to be good in ability operate the gadget. Tujuan penelitian ini adalah mendeskripsikan efektivitas media pembelajaran yang menghasilkan media valid, efektif dan praktis. Berkembangnya komunikasi dan teknologi menuntut guru untuk lebih aktif dan kreatif dalam melaksanakan pembelajaran di kelas. Guru bisa mengembangkan media pembelajaran yang mampu meningkatkan hasil belajar siswa. Sampel uji coba penelitian ini adalah siswa kelas X di MAN 1 Mojokerto. Penelitian ini menggunakan metode penelitian 4-D yang dipersingkat menjadi 3-D. Teknik pengumpulan data yang digunakan meliputi wawancara pada guru matematika, soal pretest dan posttest. Instrumen yang digunakan penelitian ini meliputi panduan penggunaan media, bahan ajar, lembar validasi, angket respon peserta didik dan tes. Hasil penelitian ini menunjukkan bahwa rata-rata validasi panduan penggunaan media dan bahan ajar adalah 95,15%, selain itu validator juga memberikan penilaian pada lembar angket respon sebesar 97,5%. Hal ini menyatakan bahwa panduan media, bahan ajar dan angket respon sangat valid. Hasil rata-rata nilai N-Gain peserta didik sebesar 0.96, berdasarkan skala kriteria N-Gain menunjukkan kriteria tinggi sehingga media dikatakan efektif dan hasil perhitungan respon angket peserta didik menunjukkan tiap poin pernyataan lebih besar dengan 70% sehingga peserta didik dapat dikatakan baik dalam kemampuan mengoperasikan gadget.